2014
DOI: 10.1590/0074-0276140312
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of the hydroethanolic extract and biflavonoids isolated from Selaginella sellowii on Leishmania (Leishmania) amazonensis

Abstract: This study is the first phytochemical investigation of Selaginella sellowii and demonstrates the antileishmanial activity of the hydroethanolic extract from this plant (SSHE), as well as of the biflavonoids amentoflavone and robustaflavone, isolated from this species. The effects of these substances were evaluated on intracellular amastigotes of Leishmania (Leishmania) amazonensis, an aetiological agent of American cutaneous leishmaniasis. SSHE was highly active against intracellular amastigotes [the half maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…Antimalarial hit compounds against the chloroquine resistant strains included compounds 8 (IC 50 : 0.95 μg/ml; Azebaze et al, ); 34 (IC 50 : 2.94 μM; Ganesh et al, ); 62 (IC 50 : 1.7 μM); 63 (IC 50 : 2.1 μM; De Monbrison et al, ); and 77 (IC 50 : 0.08 μg/ml; SI: 375 MRC‐5 cells; Konziase, ). In cutaneous leishmaniasis, the hit compounds included compounds 30 (IC 50 : 4.3 μM; SI: 18.3, macrophage cells; Fonseca‐Silva et al, ); 34 (IC 50 : 0.7 μM; SI: 10, macrophage cells; Montrieux et al, ); 92 (IC 50 : 0.2 μM; SI: 22, J774.A1 cells; Rizk et al, ); 95 (IC 50 : 8.1 μM; SI: 24.6, macrophage cells); and 96 (IC 50 : 3.2 μM; SI: 39.6, macrophage cells; Lage et al, ). Some other antileishmanial compounds with low IC 50 , that is, compounds 7 (IC 50 : 0.1390 μM); 103 (IC 50 : 0.0513 μM); and 104 (IC 50 : 0.0446 μM; Gontijo et al, ), were also nominated as hit compounds.…”
Section: Critical Assessment and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimalarial hit compounds against the chloroquine resistant strains included compounds 8 (IC 50 : 0.95 μg/ml; Azebaze et al, ); 34 (IC 50 : 2.94 μM; Ganesh et al, ); 62 (IC 50 : 1.7 μM); 63 (IC 50 : 2.1 μM; De Monbrison et al, ); and 77 (IC 50 : 0.08 μg/ml; SI: 375 MRC‐5 cells; Konziase, ). In cutaneous leishmaniasis, the hit compounds included compounds 30 (IC 50 : 4.3 μM; SI: 18.3, macrophage cells; Fonseca‐Silva et al, ); 34 (IC 50 : 0.7 μM; SI: 10, macrophage cells; Montrieux et al, ); 92 (IC 50 : 0.2 μM; SI: 22, J774.A1 cells; Rizk et al, ); 95 (IC 50 : 8.1 μM; SI: 24.6, macrophage cells); and 96 (IC 50 : 3.2 μM; SI: 39.6, macrophage cells; Lage et al, ). Some other antileishmanial compounds with low IC 50 , that is, compounds 7 (IC 50 : 0.1390 μM); 103 (IC 50 : 0.0513 μM); and 104 (IC 50 : 0.0446 μM; Gontijo et al, ), were also nominated as hit compounds.…”
Section: Critical Assessment and Discussionmentioning
confidence: 99%
“…Among six flavonoids ( 27 , 87 – 91 ) isolated from Renealmia thyrsoidea and evaluated for antileishmanial activity against L. amazonensis , 90 showed moderate inhibitory effects (IC 50 : 23.1 μM), whereas amphotericin afforded an IC 50 value of 0.15 μM (Cabanillas et al, ). Amentoflavone ( 92 ) and robustaflavone ( 93 ) (isolates of Selaginella sellowii ) were effective against L. amazonensis (incubation time: 72 hr), with IC 50 values of 0.1 μg/ml (SI: 22 and 30 for J774.A1 and NIH/3 T3 cells, respectively) and 2.8 μg/ml (SI: 9.1; J774.A1 cells), respectively, compared with amphotericin B (0.03 μg/ml; Rizk et al, ). Sandjo et al () reported the antileishmanial activity of 6,8‐diprenyleriodictyol ( 94 ; IC 50 : 12.38 μg/ml; albeit not selective vs. THP‐1 cells) against intracellular amastigotes of L. amazonensis , whereas amphotericin B displayed IC 50 value 0.07 μM.…”
Section: Natural Flavonoids As Potential Leads For the Treatment Of Mmentioning
confidence: 99%
“…Our findings show that the size of the lesion and the parasitic load is smaller in MEBA-treated mice than untreated mice. It has been reported that flavonoids isolated from Selaginella sellowi, amentoflavone (0.1 μg/mL) and robustoflavone (2.8 μg/mL), have anti-leishmanial activity on amastigotes of L. amazonensis (Rizk et al, 2014). In addition, previous reports demonstrated the antileishmanial activity of quercetin, quercetrin and isoquercetrin, as they inhibit recombinant arginase from L. amazonensis at an LC 50 of 4.3, 10.0 and 3.8 μM, respectively (Da Silva et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noticed that 3 was reported to be active against the intracellular amastigotes (peritoneal macrophages from BALB/c mice were used) of other species (L. amazonensis). [18] This fact could be explained again, by the strain specific expression of ABC transporters, known to occur in Leishmania. [28]…”
Section: Antiparasitic Activities Of the Biflavonesmentioning
confidence: 99%